Tranformasi Gaya Tari Piso Surit Di Kabupaten Langkat - Irwansyah Irwansyah (Universitas Negeri Medan, 2017)
This study aimed to describe the transformation of dance styles Piso Surit located in Langkat District of done. In this discussion the use of theories related research topics such as the theory of transformation and the theory of style. The method used qualitative methods, population research traditional leaders, cultural figures and artist. File collection techniques in clude field observation, interviews, documentation, and literature study. Based on this study, it can be seen that dance Piso Surit in Langkat undergo transformation style, a style of dance that looks more open and energetic, it isinfluenced by several factors,namely:revolution, social change takes place rapidly result in changes to the dance Piso Surit, in addition to other factor such as the revolution of the internal and exsternal factors. Interna : the lack of attention from the public Karo so that the culture gradually changed mainly in art dance Piso Surit. External:Malay society is a tribal dominated area Langkat causing people Karo absorb the malay culture, one of which happens to dance Piso Surit community Karo who was in Langkat.Keyword: Revolution, Karo tribe Society, Society Malays